1993
DOI: 10.1007/bf00034197
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium root infection of container-grown Douglas-fir: effect on survival and growth of outplanted seedlings and persistence of the pathogen

Abstract: Application . Results of this study indicate Douglas-fir seedlings with low levels of Fusarium infection in their roots will grow and survive as well as non-infected seedlings after outplanting on a forest site .Abstract . Greenhouse-grown Douglas-fir (Pseudotsuga menziesii var . glauca [Beissn.] Franco) seedlings with roots infected with either Fusarium oxysporum Schlect. or Fusarium proliferatum (Matsushima) Nirenberg were outplanted on a forest site in northern Idaho, U .S .A . No resident Fusarium populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…shown not to result in persistent post-planting infection or mortality (Smith et al 1965, Dumroese et al 1993b, Axelrood et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…shown not to result in persistent post-planting infection or mortality (Smith et al 1965, Dumroese et al 1993b, Axelrood et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…For example, depending upon the outplanting site, the percentage survival of Scots pine and Norway spruce seedlings has varied from 40 to 85% (SAKSA et al 1990;RIKALA 1992RIKALA , 1994. (DUMROESE et al 1993). Despite this, no studies have been made in Finland to determine the effect of nursery-acquired diseases on conifer seedling mortality after outplanting.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, no studies have been made in Finland to determine the effect of nursery-acquired diseases on conifer seedling mortality after outplanting. Studies made in the USA and Canada showed that mortality of outplanted seedlings, which had acquired root rot in the nursery, varied depending on the pathogen and the symptoms which were present at outplanting (HANSEN et al 1980;SAUNDERS et al 1992;DUMROESE et al 1993;BARNARD 1994). For example, the mortality of Douglas fir (Pseudotsuga menziesii (Mirb.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…France, or spruce, Picea spp., in North America (Landis 1989;Sutherland et al 1989;Hamm et al 1990) and Europe (Galaaen and Venn 1979;Perrin and Gomez 1991). Although, there is a substantial amount of information available on Fusarium, Cylindrocarpon and Pythium incidence in containergrown seedlings (Sutherland et al 1989,Unestam et al 1989Liljaet al 1992;Dumroese et al 1993), the prevalence and potential importance of these fungi on asymptomatic container-grown seedlings (Landis 1989) remains largely unknown. Although, there is a substantial amount of information available on Fusarium, Cylindrocarpon and Pythium incidence in containergrown seedlings (Sutherland et al 1989,Unestam et al 1989Liljaet al 1992;Dumroese et al 1993), the prevalence and potential importance of these fungi on asymptomatic container-grown seedlings (Landis 1989) remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%